Vanadium, Ruthenium and Copper Compounds : A New Class of Nonplatinum Metallodrugs with Anticancer Activity - León, Ignacio Esteban (2016)
Cancer is a group of diseases involving abnormal cell growth. The cells grow uncontrollably with the potential to invade and spread to other parts of the body. This disease is one of the principal death causes in the world, thus becoming a significant topic of scientific research. On the other hand, transition metals play a fundamental role in different living systems. In particular, Metallodrugs represent new and powerful tools for diverse therapeutic applications. To date, various metallodrugs display interesting biological activities for chemotherapy. In this field, cisplatin was the first inorganic compound with high relevance in cancer treatment. This compound was a leader agent in clinical use. Toxicity and resistance problems trigger the development of other platinum drugs with better clinical perspective and also raise the scientific interest for the putative antitumor properties of V, Ru and Cu compounds. Several scientific articles show that complexes of these metals are the new metal-based drugs used in the treatment of several cancers, such us, lung, colon, breast, bladder, etc. In this review we recapitulate current information and new advances on antitumor in vitro effects of several organic and inorganic compounds derived from copper, ruthenium and vanadium. These metal derived compounds targeting DNA or cell proteins involved in cell signaling pathways related to cancer. The mechanisms of cell death of these metallodrugs have also been comprehensibly reviewed. The knowledge of these mechanisms of death and the relationship between chemical structure and biological activity may be useful for the design of new metal-based drugs with promising pharmacologic applications as anticancer agents.